Synthesis and biological evaluation of the novel chrysin prodrug for non-alcoholic fatty liver disease treatment - Zhang, Ruiming; Gao, Chuanyue; Hu, Mingxing; Wang, Xingxing; Li, Shuoyuan; An, Zhenmei; Yang, Xifei; Xie, Yongmei (Frontiers in Pharmacology, 2024)
Background: Chrysin (5,7-dihydroxyflavone) is a natural flavonoid that has been reported as a potential treatment for non-alcoholic fatty liver disease (NAFLD). However, extensive phase II metabolism and poor aqueous solubility led to a decrease in the chrysin concentration in the blood after oral administration, limiting its pharmacological development in vivo. Methods: In the present study, we synthesized a novel chrysin derivative prodrug (C-1) to address this issue. We introduced a hydrophilic prodrug group at the 7-position hydroxyl group, which is prone to phase II metabolism, to improve water solubility and mask the metabolic site. Further, we evaluated the ameliorative effects of C-1 on NAFLD in vitro and in vivo by NAFLD model cells and db/db mice. Results:In vitro studies indicated that C-1 has the ability to ameliorate lipid accumulation, cellular damage, and oxidative stress in NAFLD model cells. In vivo experiments showed that oral administration of C-1 at a high dose (69.3 mg/kg) effectively ameliorated hyperlipidemia and liver injury and reduced body weight and liver weight in db/db mice, in addition to alleviating insulin resistance. Proteomic analysis showed that C-1 altered the protein expression profile in the liver and particularly improved the expression of proteins associated with catabolism and metabolism. Furthermore, in our preliminary pharmacokinetic study, C-1 showed favorable pharmacokinetic properties and significantly improved the oral bioavailability of chrysin. Conclusion: Our data demonstrated that C-1 may be a promising agent for NAFLD therapy.